Homoiosis Theo Problems in Rabbinic and Hellenistic Judaism - Gudelytė, Kristina (Problemos, 2003)
Homoiosis Theo(imitatio dei) - one of the most popular religious-philosophical categories, which allows to compare the similarities and differences between Greek and Jewish cultures, because it includes such basics as God, man and being. Both Greeks and Jews have their parallel moments in historical sources, but monotheistic conception was the point of departure for development in two different ways. Philo's exegesis could be described as the culmination of syncretism tendency, in which the ideas of Hellenistic Judaism took root and spread. His works are written in an exceedingly rich Greek and show great influence of Greek philosophy, but in spite of it Hellenistic exegete often views religious perfection as independent of philosophical perfection; in his exegesis the most important accents are submission, devotion, theocentrical view, grace, faith and theonomy. In discussing God's essence Philo maintains an extreme transcendentalism, surpassing even of Plato, but in contradiction to himself, he writes that man has to strive to know God and God is the only object worth knowing. The reconciliation between soul and God is described by Philo in two ways: God's descent into human soul and the soul's ascent to God. The Patriarchs are the archetypes of divine law, meaning that God disclosed to them His higher spheres. In spite of Philo's loyalty to his ancestor's religious views and some traces of his influence on Midrash, the greatest influence he made on Church Fathers, who adopted many of his concepts.
Keywords: assimilation to God; God; being; theocentrism; transcendence